Effect of gestational weight gain on placental weight: A single tertiary referral center study of Japanese women. Issue 12 (15th October 2021) - Jin, Toki; Kyozuka, Hyo; Fukuda, Toma; Fujimori, Mimori; Murata, Tsuyoshi; Nomura, Shinji; Suzuki, Daisuke; Nomura, Yasuhisa; Imamura, Takashi; Yasuda, Shun; Yamaguchi, Akiko; Fujimori, Keiya
Abstract: Aim: The effect of gestational weight gain on placental weight has not been elucidated. We aimed to examine the effect of body weight gain during pregnancy on the Japanese standardized z‐score of placental weight, based on the pre‐pregnancy body mass index. Methods: This retrospective cohort study included Japanese women with singleton pregnancies who gave birth during 2013–2019 at Ohta Nishinouchi Hospital. Participants ( n  = 3610) were categorized by their pre‐pregnancy body mass index: G1 (<18.5 kg/m 2 ), G2 (18.5 to <20.0 kg/m 2 ), G3 (20.0 to <23.0 kg/m 2 ), G4 (23.0 to <25.0 kg/m 2 ), and G5 (≥25.0 kg/m 2 ). Multiple linear regression analysis was used to identify associations between insufficient or excessive gestational weight gain in each body mass index category and z‐score of placental weight, with adjustments for maternal age, assisted reproductive technology, and maternal pre‐pregnancy conditions, such as hypertension, diabetes mellitus, myoma uteri, and uterine anomalies. Results: Among the 3610 women assessed, 479, 692, 1292, 435, and 711 were in G1–G5, respectively. In G1, G3, and G4, excessive weight gain increased the placental weight z‐score ([B: 0.50, 95% confidence interval [CI]: 0.23–0.76], [B: 0.19, 95% CI: 0.19–0.33], and [B: 0.18, 95% CI: 0.10–0.26]). Insufficient weight gain decreased the placental weight z‐score in G3 (B: −0.19, 95% CI: −0.33 to −0.06) and G4 (B: −0.21, 95% CI: −0.29 to −0.13) women. Conclusion: The effect of weight gain during pregnancy on placental size varies by pre‐pregnancy body mass index. This result may guide personalized pre‐conception counseling to improve the outcomes of offspring.